Is outcome related to movement variability in golf? - Tucker, C. B.; Anderson, R.; Kenny, I. C. (Sports Biomechanics, 2013)
The aim of this study was to develop a method to quantify movement variability in the backswing and downswing phase of the golf swing and statistically assess whether there was any relationship between movement variability and outcome variability. Sixteen highly skilled golfers each performed 10 swings wearing retro-reflective markers which were tracked by a three-dimensional (3D) motion analysis system operating at 400 Hz. Ball launch conditions were captured using a launch monitor. Performance variability was calculated for each body marker based on a scalene ellipsoid volume concept which produced a score representative of the 3D variability over the 10 trials. Outcome variability was quantified as the coefficient of variation of ball velocity for the 10 trials. The statistical analysis revealed no significant correlations between performance variability for each marker trajectory and outcome variability. Performance variability in the backswing or downswing was not related to ball velocity variability. It was postulated that individual players used their own strategies in order to control their performance variability, such that it had no effect on outcome variability.